Against the wind: A load-bearing, yet durable, kite inspired by insect wings. (15th January 2021) - Khaheshi, Ali; Tramsen, Halvor T.; Gorb, Stanislav N.; Rajabi, Hamed
Abstract: Durability and load-bearing are difficult to be combined in engineering systems. Hence, in majority of man-made structures, the two characteristics are typically mutually exclusive. Nature, however, has provided us with design strategies, through which many biological systems have overcome this conflict. Insect wings represent a striking example of such a combination. A key to this lies in the presence of vein joints. Here we 3D printed bio-inspired joints, akin to those of insect wings and tested their mechanical performance under both static and cyclic loadings. We used the so-called 'flexible joints', which had a high durability, and engineered them to further enhance their load-bearing capacity. We then implemented them into the design of the first 3D printed bio-inspired kite. The manufactured kite showed a stable flight and withstood loads induced by strong wind gusts without failure. The concept developed here can be applied to other engineering designs that pursue a compromise between load-bearing and durability. At the end, we used our data to better understand the complexities of insect wings with respect to their local and global deformations and fracture resistance. Graphical abstract: Unlabelled Image Highlights: We developed a bio-inspired design strategy to combine two mutually exclusive characteristics of loading-bearing and durability. Our design strategy is purely structural and, therefore, can be easily modified and implemented in engineering systems. Using the developed strategy, we designed and fabricated the first bio-inspired 3D printed kite that can withstand strong wind gusts. The example of the kite confirmed the efficiency of our bio-inspired strategy in practice. A similar design principle could be used to develop load-bearing, yet durable, engineering structures.